THE EFFECT OF INFLATION, INTEREST RATE, AND EXCHANGE RATE ON STOCK RETURNS IN FOOD & BEVERAGES COMPANIES - Suharyanto, Suharyanto; Zaki, Achmad (Jurnal Aplikasi Manajemen, 2021)
The purpose of this study was to determine the effect of technical information on stock returns partially. Risk and return are interrelated. The greater the return, the greater the risk obtained. However, if these risks are managed, the risks that will occur can be controlled properly. Several things need to be considered in making investment decisions, namely, by analyzing fundamental information and technical information, including inflation, exchange rates, interest rates, and their effect on stock returns. The method used in this study uses quantitative methods. This study indicates that inflation has a significant negative effect on stock returns, interest rates have no effect on stock returns, and the exchange rate has a significant negative effect on stock returns. Further researchers are expected to pay attention to the influence of other factors that can affect price movements and company stock returns.